Anti-CD20 monoclonal antibodies: reviewing a revolution - J. M. L. Casan; J. Wong; M. J. Northcott; S. Opat (Taylor & Francis Group, 2018)
Since the inception of rituximab in the 1990s, anti-CD20 monoclonal antibodies have revolutionised the treatment of B cell hematological malignancies and have become a cornerstone of modern gold-standard practice. Additionally, the potent efficacy of these agents in depleting the B cell compartment has been used in the management of a broad array of autoimmune diseases. Multiple iterations of these agents have been investigated and are routinely used in clinical practice. In this review, we will discuss the physiology of CD20 and its attractiveness as a therapeutic target, as well as the pharmacology, pre-clinical and clinical data for the major anti-CD20 monoclonal antibodies: rituximab, obinutuzumab and ofatumumab.